Simplify (2n + 5) - (3n + 7) + (4n - 9).

(2n + 5) - (3n + 7) + (4n - 9) = (-n - 2) + (4n - 9) = 3n - 11

Question

Asked 6/29/2011 10:13:09 AM

Updated 10/10/2016 7:27:02 AM

1 Answer/Comment

Rating

3

(2n + 5) - (3n + 7) + (4n - 9)

= (-n - 2) + (4n - 9)

= 3n - 11

= (-n - 2) + (4n - 9)

= 3n - 11

Added 10/10/2016 7:26:58 AM

This answer has been confirmed as correct and helpful.

Simplify 5t + (t - 3) - [(7t + 5) - (8 - 3t)].

Question

Expert Answered

Updated 5/20/2014 2:22:45 PM

1 Answer/Comment

5t + (t - 3) - [(7t + 5) - (8 - 3t)];

5t + (t - 3) - (10t - 3);

5t - 9t = -4t

5t + (t - 3) - (10t - 3);

5t - 9t = -4t

Added 5/20/2014 2:22:45 PM

This answer has been confirmed as correct and helpful.

49t6 - 4k8 factored
**Weegy:** There is one special case for factoring that you may or may not need, depending upon how your book is structured and how your instructor intends to teach factoring quadratics. I call it "factoring in pairs". (More)

Question

Not Answered

Updated 7/10/2014 6:42:45 AM

1 Answer/Comment

49t^6 - 4k^8 = -(2 k^4-7 t^3) (2 k^4+7 t^3)

Added 7/10/2014 6:42:45 AM

This answer has been confirmed as correct and helpful.

27,208,703

questions answered

There are no comments.